(untitled) (International Journal of Biology and Chemistry, 2026)
This study investigates the influence of radical initiator chemistry on the synthesis and structural evolution of pH-responsive gum arabic–acrylamide (GA-g-AM) hydrogels intended for drug-delivery applications. Gum arabic was used as a natural polysaccharide backbone, and acrylamide was grafted via a free-radical mechanism to form crosslinked hydrogel networks. A controlled comparative evaluation of ammonium persulfate (APS) and azobisisobutyronitrile (AIBN) was performed under identical synthesis conditions to evalute the specific influence of initiator type on hydrogel network formation. FTIR, SEM, and XRD analyses confirmed successful copolymerization and revealed differences in structural organization and packing density between the two systems. Swelling experiments demonstrated clear pH-responsive behavior, with maximum equilibrium swelling observed at pH 2. APS-initiated hydrogels exhibited an equilibrium swelling of 720 ± 5%, whereas AIBN-initiated systems reached 1026 ± 5%, indicating differences in crosslink distribution and internal network structure. APS-generated hydrogels showed a more compact morphology, while AIBN-based systems formed comparatively looser networks with higher water uptake. Overall, the results indicate that APS promotes the formation of structurally more organized and compact GA-based hydrogel networks, highlighting the decisive role of initiator chemistry in tailoring natural polymer-derived drug-delivery systems. Keywords: gum arabic, acrylamide, APS, AIBN, graft copolymerization, hydrogel swelling